2011
DOI: 10.1021/jp2076935
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Folding Pathways of a β-Sheet Miniprotein

Abstract: Several methods have been developed in the past few years for the analysis of molecular dynamics simulations of biological (macro)molecules whose complexity is difficult to capture by simple projections of the free-energy surface onto one or two geometric variables. The locally scaled diffusion map (LSDMap) method is a nonlinear dimensionality reduction technique for describing the dynamics of complex systems in terms of a few collective coordinates. Here, we compare LSDMap to two previously developed approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 43 publications
11
56
0
Order By: Relevance
“…The last conformations that come in equilibrium with the others are the Ch-curl conformations, which are less stable than the antiparallel β-strands and more difficult to form dynamically because of the distant N-and C-terminal strands. The observed hierarchy of the establishment of equilibrium between the characteristic conformations is in good agreement with the results of the previous studies 6,11,12,25,28,[30][31][32]45 and has allowed further insight into the process of beta3s folding. One issue of particular interest is the difference between the Cs-or and Ns-or pathways, which has been indicated in the early work 25 and confirmed in the later, the first-passage folding studies: 11,12 although Cs-or and Ns-or conformations are "symmetrical" in that each of them has one hairpin formed and the other unstructured, the Ns-or pathway prevails.…”
Section: Resultssupporting
confidence: 90%
“…The last conformations that come in equilibrium with the others are the Ch-curl conformations, which are less stable than the antiparallel β-strands and more difficult to form dynamically because of the distant N-and C-terminal strands. The observed hierarchy of the establishment of equilibrium between the characteristic conformations is in good agreement with the results of the previous studies 6,11,12,25,28,[30][31][32]45 and has allowed further insight into the process of beta3s folding. One issue of particular interest is the difference between the Cs-or and Ns-or pathways, which has been indicated in the early work 25 and confirmed in the later, the first-passage folding studies: 11,12 although Cs-or and Ns-or conformations are "symmetrical" in that each of them has one hairpin formed and the other unstructured, the Ns-or pathway prevails.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, these pathways are corroborated by previous work (there is an extensive literature on this topic, see e.g. [17]–[20]), which posits that Loop 1 formation is initiated at near the loop region and “zippers up” via hydrogen bonding, and Loop 2 is formed by a hydrophobic collapse (a transition which may be inferred from the 404 → 600 edge).…”
Section: Awe Resultssupporting
confidence: 81%
“…In practice, we have found that values near the low boundary of the region produce plots with more clearly visible clusters. We refer the reader to the work of Clementi et al 34,58,59 for additional considerations and algorithmic suggestions for the choice of . Table II indicates how well formed are the clusters of the optimal (k = 16) k-means partitioning.…”
Section: Appendix A: Choice Of Epsilonmentioning
confidence: 99%